Coronary bypass using bilateral internal mammary arteries in an achondroplast. (January 2015) - Alassal, Mohamed Abdulwahab; Youssef, Mostafa; Koudieh, Mohammed
Coronary bypass grafting for ischemic heart disease in achondroplastic dwarfs is very rare. Shortage of veins and inadequate vein quality may cause difficulties during surgery. Only 2 cases of coronary bypass surgery in an achondroplastic dwarf, in which the left internal mammary artery and vein grafts were used, have been reported. We describe the case of a 55-year-old male achondroplastic dwarf who had triple-vessel coronary disease and underwent successful coronary bypass surgery using one saphenous vein graft and bilateral internal mammary artery grafts. The anatomic and surgical challenges in achondroplasia are highlighted.